The world of Matisse, 1869-1954 - Russell, John (Time-Life Library of Art, 1972)
Henri Matisse was schooled as a lawyer, and did not take up art seriously until his early twenties. But when he did, he pursued his training with the logic and determination of an attorney defending a client. He was sure of what he wanted to do, and he was not afraid to express opinions. On his first morning at the Ecole des Beaux-Arts in Paris, he strode into class with his hat on. When his annoyed teacher objected, Matisse is supposed to have calmly informed him, "I'll take it off as soon as you shut the window. There is a strong draft in here."